PENGARUH KOMITE AUDIT, UKURAN PERUSAHAAN, LEVERAGE, DAN PENYAJIAN OTHER COMPREHENSIVE INCOME TERHADAP MANAJEMEN LABA PERUSAHAAN PROPERTI INDONESIA - Herry Winarto; JMV Mulyadi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to examine the influence of audit committees, firm size, leverage and disclosure of other comprehensive income on earnings management in property companies listed on the Indonesia Stock Exchange 2012-2015. This study uses quantitative data that has been published in Indonesia Stock Exchange (BEI). Where the sample used in this study as many as 153 consisting of 201 companies that meet the criteria of research, because this study using purposive sampling method in the selection of samples. While the method of data analysis using SPSS regression version 22. The test results are done using fixed effect model. The result of partial test (t test) obtained by company size, and leverage, influence to earnings management, while audit committee and other comprehensive income have no effect to earnings management. Where the error rate used is 5% or 0.05 at a significant level of 95%.